2016
DOI: 10.18006/2016.4(2).218.224
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis, antimicrobial screening and hypoglycemic effect of some selected medicinal plant extract from Oman

Abstract: In present study phytochemical screening and antimicrobial potential of three Omani traditional medicinal plants i.e. Ajuga iva, Pteropyrum scoparium and Rhazya stricta was carried out. The information generated from study will be helpful in drug administration and developing commercial drug form these studied traditional plants. All three selected plants were air dried under natural condition and phytochemical screenings were carried out under laboratory conditions. Antimicrobial properties of the selected pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The results of the study revealed that the selected plants had reduced the blood sugar level of the treated mice; the extracts of R. stricta and A. iva had more pronounced effects than P. scoparium . The hypoglycemic effect of R. stricta extract may be due to its potentiating effect on the insulin-releasing mechanism; this suggests a mode of action resembling the mechanism of sulfonylureas [ 25 ].…”
Section: Medicinal Plants With Potential Antidiabetic Activity In mentioning
confidence: 99%
“…The results of the study revealed that the selected plants had reduced the blood sugar level of the treated mice; the extracts of R. stricta and A. iva had more pronounced effects than P. scoparium . The hypoglycemic effect of R. stricta extract may be due to its potentiating effect on the insulin-releasing mechanism; this suggests a mode of action resembling the mechanism of sulfonylureas [ 25 ].…”
Section: Medicinal Plants With Potential Antidiabetic Activity In mentioning
confidence: 99%